Health care transition experiences of young adults with medical complexity - Rhonda G. Cady; Tori Bahr; Carrie Au-Yeung; Sera Kinoglu; Megan Lutz; Mark Jankowski (Health Care Transitions)
Background: Transition from pediatric to adult healthcare and services is an important event in the life course of all youth, including youth living with medical complexity. Data from the National Survey of Children’s Health indicates less than 20 % of youth receive health care transition services. The goal of our study was understanding the support, tools and resources that facilitate successful health care transition of young adults living with medical complexity. Methods: Young adults living with medical complexity and their parents shared their lived experience of ‘what worked’ and ‘what is needed’ for successful health care transition during focus group sessions. Content analysis of transcripts used an iterative and deductive approach guided by a priori themes. Findings: The voices of ten young adults and fourteen parents were shared during three virtual focus group sessions. They described health care transition (HCT) as an individualized process with success relying on consistent, clearly-defined and systemwide guidelines and resources. Moving from pediatric/family-focused care to adult/patient-focused care requires increased self-management and young adults often felt under-prepared for this role. Support from formal transition coordinators would improve communication between the multiple health, county/state agency and education systems involved during the transition period. Conclusions: Understanding the support, tools, and resources specifically needed by young adults with medical complexity for successful pediatric to adult health care transition is a critical first step in addressing the documented lack of transition services for this vulnerable population. This includes formal peer support programs for young adults with medical complexity and their parents.